Obstructive Sleep Apnea Is Associated with Worsened Hospital Outcomes in Children Hospitalized with Asthma - Jasmine Khatana; Aravind Thavamani; Krishna Kishore Umapathi; Senthilkumar Sankararaman; Aparna Roy (MDPI AG, 2024)
Background: Studies have shown a bidirectional relationship between asthma and obstructive sleep apnea (OSA). However, there is a paucity of national-level data evaluating the impact of OSA on hospital outcomes in pediatric hospitalizations for asthma. Methods: We analyzed the National Inpatient Sample and Kids Inpatient Database to include all pediatric hospitalizations with a primary diagnosis of asthma between 2003-2016. Using ICD codes, the pediatric asthma cohort was divided into two groups: those with and those without a concomitant diagnosis of OSA. The primary outcomes were in-hospital mortality and the need for mechanical ventilation. The secondary outcomes were the lengths of each hospital stay and total hospitalization charges. Results: We analyzed 1,606,248 hospitalizations during the 14-year study period. The overall prevalence rate of OSA was 0.7%. Patients with asthma and OSA were significantly older (8.2 versus 5.9 years) and were more often male, p < 0.001. The OSA group had several increased comorbidities. The overall mortality rate was 0.03%, and multivariate regression analysis showed that OSA was associated with 4.3 times higher odds of in-hospital mortality (95% CI: 2.4 to 7.6, p < 0.001). Furthermore, OSA was associated with a 5.2 times greater need for mechanical ventilation (95% CI: 4.8 to 5.5, p < 0.001). Linear regression analyses demonstrated that OSA independently contributed an additional 0.82 days to the hospital stay length (95% CI: 0.79 to 0.86, p < 0.001) and an extra 10,479 USD (95% CI: 10,110 to 10,848, p < 0.001) in hospitalization charges. Conclusion: OSA in children admitted with asthma is associated with poor hospital outcomes such as increased mortality risk, the need for mechanical ventilation, and increased healthcare utilization.